Expansion Strategies of International Hotel Companies in Central Asia - Altynai Moldasheva; Anuarbek Aymen; Turgay Ekici; Kutay Oktay (Journal of Silk Road Tourism Research)
The active contribution of international tourism to the economies of Central Asian countries has gradually increased in recent years with the growth of the sector and the importance that states attach to tourism. States in the region seem to be attracting the attention of global tourism through marketing methods and promotional activities. Recent infrastructure investments done by local governments also help to increase tourist numbers and tourism revenues. This, therefore, affects the investment and expansion strategies of international hotel companies operating in the region. This study focuses on the expansion strategies of international companies in Central Asia. The case study method was used to analyze the expansion strategies of these global companies operating in the region. Research findings reveal that international hotel companies increase the number of their hotels in the region by maintaining various expansion strategies.